Bauran Komunikasi Pemasaran Pariwisata dalam Meningkatkan Jumlah Wisatawan : Studi pada Destinasi Air Terjun Curup Tujuh Kampung Marga Jaya pada Destinasi Selagai Lingga Kabupaten Lampung Tengah Tahun 2024 - Rika Agustina; Immawati Asniar; Achmadi Achmadi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
This study aims to analyze the implementation of tourism marketing communication mix in increasing the number of visitors at Curup Tujuh Waterfall Destination, Marga Jaya Village, Selagai Lingga District, Central Lampung Regency in 2024. The research background is based on the gap between the high natural tourism potential of the destination and the fluctuation in tourist arrivals. This study employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, field observations, and documentation studies involving destination managers, village officials, local communities, and tourists. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the tourism marketing communication mix has not been optimal and integrated. Each element of marketing communication, including advertising, sales promotion, public relations, digital marketing, and word-of-mouth communication, has been applied partially without a clear strategic plan. The use of digital media has not been professionally managed and has not yet succeeded in building a consistent destination image. The increase in tourist arrivals is more influenced by seasonal factors rather than by the effectiveness of marketing communication strategies. Limited message integration and weak collaboration among stakeholders have become major constraints in enhancing the destination’s competitiveness. This study concludes that strengthening an integrated, collaborative, and experience-oriented marketing communication mix is essential to achieve sustainable growth in tourist visits.